Private bribery in Paraguayan criminal law (Journal on studies and research of academic knowledge, 2022)
Since democratic times, one of the greatest challenges for Paraguay has been the prosecution of acts of corruption, verified both in the public and private sectors, due to their international reach. Therefore, in 2019 the Congress of the Republic promulgated several laws that sanction crimes of corruption, including Law 6452, which typifies private bribery, an unusual figure in national private law. The objective of this paper is to determine the importance of incorporating private bribery into Criminal Law, as well as the difficulties in its application, in view of the multiplicity of factors that influence this purpose, therefore; The need arises to establish control mechanisms within the entities receiving the law. The research is explanatory, in terms of the relevance of private bribery in domestic law, in terms of its legal-economic repercussions, a deductive approach was worked, with respect to the consulted bibliography, a mixed scheme, applying surveys and interviews to groups of people linked to the legal and economic field, finding divergent positions in relation to the intervention of Criminal Law in the private sector, perceiving uncertainty in relation to the effective applicability of the norm and concern in relation to the evidentiary scheme of the same, as well as in terms of controls and their effectiveness in small businesses.
Keywords: Private bribery; Corruption; Applicability of the law; Difficulties in law implementation